Mini-Descemet Membrane Endothelial Keratoplasty for the Early Treatment of Acute Corneal Hydrops in Keratoconus. Issue 8 (August 2019) - Bachmann, Björn; Händel, Alexander; Siebelmann, Sebastian; Matthaei, Mario; Cursiefen, Claus
Abstract : Purpose: To describe a new surgical option for the treatment of acute corneal hydrops in keratoconus and to present the first results. Methods: This is a retrospective analysis of 3 patients who presented to our clinic with a massive corneal hydrops in acute keratoconus and were treated by mini-Descemet membrane endothelial keratoplasty (DMEK). According to the size and the shape of the gap in the patient's Descemet membrane (DM), 1 DMEK graft was trephined with a round 5-mm punch. The other grafts were trimmed with a razor blade to a width of about 3 mm and a length adjusted to the length of the defect of the recipients' DM. The graft was inserted with a regular intraocular lens shooter. Correct unfolding of the graft was controlled by using intraoperative optical coherence tomography. At the end of the surgery, the graft was attached to the posterior corneal surface by a small air bubble. Thereafter, the complete anterior chamber was filled with 20% SF6 gas. Results: All 3 patients (age 32 ± 3 years on average) showed a rapid increase in uncorrected visual acuity from the logarithm of the minimum angle of resolution (LogMAR) 1.66 (±0.46) before mini-DMEK to the LogMAR 1.2 (±0.3) within 6 to 8 weeks after mini-DMEK. The thickest corneal point within the edematous cornea decreased in all 3 patients (1088 ± 280 μm before surgery vs. 630 ± 38 μm 1 week after surgery). One mini-DMEK failed in a first attempt. In this patient, the recipient DM was under strong tension and showed a pronounced dehiscence. Therefore, a small part of the recipient's DM around the preexisting gap in DM was removed before a second mini-DMEK graft was placed successfully. The other 2 patients developed partial graft detachment within 1 to 2 weeks after surgery. However, the corneas of these patients were dehydrated to physiological levels after mini-DMEK, and despite partial detachment, there was no relapse of the hydrops. Conclusions: Mini-DMEK could be helpful in patients with larger defects and detachments of DM in very ectatic corneas in the acute phase of corneal hydrops in acute keratoconus. These patients may not be successfully treated by intracameral gas application alone or in combination with pre-Descemetal sutures. Further investigations are needed to identify factors helping to decide on the best surgical approach in hydrops in acute keratoconus.